cn u help me wiv dis =) thnx

A) 9/2x-1 = x+7/x+1

B) 3/x-2 + x/x+1 = 2 (gv solution correct 2 3.s.f)

C) 1/x^2 - 16 + 2/x+4 = 3x/x-4

Posted Fri 8th June, 2012 @ 17:01 by

waqar
A) Multiply by (2x-1) and (x+1) and cancel to get

9(x+1)=(x+7)(2x-1)

9x+9=2x^2+13x-7

0=2x^2+4x-16

0=x^2+2x-8

0=(x+4)(x-2)

so x=-4or x=2

B) Do the same...

3(x+1)+x(x-2)=2(x+1)(x-2)

3x+3+x^2-2x=2(x^2-x-2)

x+3+x^2=2x^2-2x-4

0=x^2-3x-7

Solve x using quadratic formula.

C) Factorise

1/(x+4)(x-4) + 2/(x+4) = 3x/(x-4)

Multiply by (x+4)(x-4) and then cancel.

1+ 2(x-4)=3x(x+4)

1+2x-8=3x^2+12x

0=3x^2+10x+7

0=(3x+7)(x+1)

so x= -3/7 or x=-1

Answered Fri 8th June, 2012 @ 17:23 by

Dilly
k thnx dilly helped a lot =)

Answered Fri 8th June, 2012 @ 17:27 by

waqar
Answered Fri 8th June, 2012 @ 17:28 by

Dilly
Answered Fri 8th June, 2012 @ 17:30 by

waqar